The sun collective : a novel - Baxter, Charles, 1947- (Pantheon Books, 2020)
"From National Book Award finalist and "one of our most gifted writers" (Chicago Tribune), Charles Baxter, a timely and unsettling new novel about the people drawn to and unmoored by a local activist group more dangerous than it appears. Brettigan's son, a once promising actor, has gone missing, and despite the fact that his wife, Alma, knows he left on purpose, she has been searching for him all over the city. She checks the usual places, churches, storefronts, and benches, and stumbles upon a local community group with lofty goals and an enigmatic leader. Christina, a young woman rapidly becoming addicted to a boutique drug that gives her a feeling of blessedness, is inexplicably drawn to the same collective by a man who's convinced he's found direction, named Ludlow. As these five characters cross paths, a story of guilt, anxiety, and feverish hope unfolds in suburban, middle-class Minneapolis. A send-up of modern American society and the specters of its consumerism, fanaticism, and fear that haunt it, The Sun Collective captures both the mystery and violence that punctuate our daily lives"--Provided by publisher.